2017
DOI: 10.3390/ijerph14030310
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prediction of Suicide and Undetermined Death: A Pseudo-Prospective Clinical and Medico-Legal Study of Substance Abusers

Abstract: This study examines aspects of prediction of suicide and death of undetermined intent. We investigated all consecutive, autopsied patients between 1993 and 1997 who had been in contact with the Addiction Centre in Malmö from 1968 onwards. The staff was asked, shortly after autopsy but before they knew of the manner of death, if they thought the patient had committed suicide. The case records were blindly evaluated, and toxicological autopsy findings for alcohol in blood samples investigated. The specificity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…Gov, 2017) (Quello et al, 2005) (Hasin et al, 2002) and within this study, correlations were found between substances being present on toxicology and a diagnosis of depression. These results are consistent with studies that have identified that drugs increased the likelihood of accidents, suicides and homicides (Aharonovich et al, 2002;Brådvik et al, 2017;Kamali et al, 2000;Ortíz-Gómez et al, 2014) impulsivity and decreased rational thinking. (Ortíz-Gómez et al, 2014;WHO, 2017) There was a higher proportion of individuals with a diagnosis of depression who specifically had a history of taking Cocaine and Opiates.…”
Section: Discussionsupporting
confidence: 91%
“…Gov, 2017) (Quello et al, 2005) (Hasin et al, 2002) and within this study, correlations were found between substances being present on toxicology and a diagnosis of depression. These results are consistent with studies that have identified that drugs increased the likelihood of accidents, suicides and homicides (Aharonovich et al, 2002;Brådvik et al, 2017;Kamali et al, 2000;Ortíz-Gómez et al, 2014) impulsivity and decreased rational thinking. (Ortíz-Gómez et al, 2014;WHO, 2017) There was a higher proportion of individuals with a diagnosis of depression who specifically had a history of taking Cocaine and Opiates.…”
Section: Discussionsupporting
confidence: 91%
“…Alcohol at levels above 1‰ was also associated with an increased risk of self-inflicted death. This level of alcohol has also been found in suicide victims with a brittle/sensitive personality [ 44 ] and high levels of alcohol were also related to suicide among patients with suicidal ideation in a previous study on the present sample [ 38 ], both indicating disinhibition of suicidal impulses. Furthermore, there were equal rates of positive blood sampling in poisoning and violent suicides and deaths of undetermined intent and also similar rates of detection of high alcohol levels (above 1‰), regardless of violent method.…”
Section: Discussionsupporting
confidence: 80%
“…The sample has been presented in a previous study on unnatural death and drugs used in life, concluding that number of substances used in life is related to an increased risk of death of undetermined intent and heroin overdoses, but not suicide [ 37 ]. A more recent study on the same sample showed that suicidal communication was more often considered non-serious before death of undetermined intent than before suicide, and that the undetermined group also showed higher levels of alcohol in blood at autopsy [ 38 ]. The sample does not reflect the substance use pattern of today, but the physical and psychological effects we intended to study remain the same.…”
Section: Introductionmentioning
confidence: 99%